Importance of later phases in seismic tomography - Zhao, Dapeng (Physics of the earth and planetary interiors, 2019)
Seismic tomography is a powerful tool for mapping the three-dimensional structure of the Earth's interior. Tomographic images obtained in the past four decades have greatly improved our understanding of the Earth's heterogeneous structure and dynamics, which signify a revolution in Earth sciences. Most of the tomographic models are determined using the first P and S wave data generated by local earthquakes and/or teleseismic events. Five global seismic discontinuities exist in the Earth, including the Moho, the 410 km and 660 km discontinuities, the core-mantle boundary, and the inner-core boundary. In addition, local-scale seismic discontinuities are also revealed, particularly in subduction zones. These sharp discontinuities generate abundant reflected and converted seismic waves, the so-called later phases, which are identified in observed seismograms. In this article, I review the tomographic studies in the past three decades that made use of the later phase data. Because later phases have ray paths different from those of the first P and S waves, they illuminate the Earth's interior structure that is not well sampled by the first waves. Hence, the use of later phases in tomographic imaging has led to new discoveries of anomalous structures and geodynamic processes at different spatial scales, which shed new light on seismotectonics, magmatism and mantle dynamics. These practices indicate that the later phases are very important in seismic tomography, and so they should be collected from seismograms with a greater quantity and quality so as to obtain better tomographic images of the Earth's interior. •Crustal reflected waves help clarify mechanisms of large earthquakes.•Depth phases lead to off-network tomography for studying megathrust earthquakes.•Tomography with later phases provide new insight into subduction dynamics.•Mantle and core phases improve images of deep slabs and mantle plumes.